Climate governance action and corporate environmental performance: evidence from climate resilient city construction - Lu, Zhihan; Bao, Kaihua; Hu, Xiliang; Gao, Chen; Wen, Ya; Zhang, Ting (Frontiers in Environmental Science, 2025)
IntroductionPromoting the improvement of corporate environmental performance is an important micro-foundation for achieving green high-quality development.MethodsThis study takes Chinese A-share listed firms on the Shanghai and Shenzhen stock exchanges from 2011 to 2023 as the research sample, regards the climate resilient city construction (CRCC) pilot policy as a quasi-natural experiment, and employs the difference-in-differences (DID) method to empirically examine its impact on corporate environmental performance.ResultsThe empirical results show that CRCC significantly improves corporate environmental performance. This conclusion remains valid after a series of robustness tests, including the parallel trends test, placebo test, and PSM-DID. Mechanism analysis reveals that CRCC promotes the improvement of corporate environmental performance through three channels: enhancing urban environmental attention, strengthening environmental regulation intensity, and increasing corporate climate risk disclosure. Heterogeneity tests show that the policy effects are more pronounced in the southeast region of the “Hu Huanyong Line”, non-state- owned firms, and heavily polluting industries.DiscussionThis study provides empirical evidence for understanding the micro-transmission mechanism of climate resilient policies and offers insights for improving climate governance policies and promoting corporate green transitions.